COVID-19 Pandemic: Inducing Pan-Hysteria and Panic Disorder; An Overview - Arpita Aswinikumar Sahu (Institute of Medico-legal Publications Pvt Ltd, 2020)
Summary: Wuhan Municipal Health Commission, China, gave an account of a few cases of pneumoniawhich were later established as cases of the Novel Coronavirus Disease by the end of December 2019. By 4thof January, WHO reported these cases on social media and by the beginning of March WHO had declared itas a pandemic which was preceded and followed by lockdowns in various countries and had led to a scenarioof fear and panic amidst the minds of all.The coronavirus disease 2019 (COVID-19) pandemic has challenged the society in many aspects, one of thembeing the psychosocial aspect. The stress due to the pandemic could produce worry and fear about health foroneself, family members and friends. Even changes in sleeping or eating patterns, the worsening of chronichealth problems,unavailability of alcohol, tobacco or other drugs in the market due to shutting down ofmanufacturing units and problems in concentration are among the possible etiologies of a precipitating panicdisorder. Containment measures such as lockdown and isolationcan also precipitate psychiatric illnessesand morbidities such aspanic disorder, depression, anxiety and suicidal tendencies.COVID-19 may causeor exacerbate even the existing psychiatric illnesses or existing panic disorder in individuals which couldlead to physiological symptoms like palpitations, sweating, shortness of breath and a decreased sense ofwellbeing. It gives a feeling of impending doom or danger and is followed by intense fear which can all takeplace when one is facing such a pandemic.Conclusion: The COVID-19 pandemic has not only had physical but even mental and psychosocial impacts.New mental health challenges may arise owing to this pandemic.